3(x-5)+x=4(x-4)+1

Simple and best practice solution for 3(x-5)+x=4(x-4)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-5)+x=4(x-4)+1 equation:


Simplifying
3(x + -5) + x = 4(x + -4) + 1

Reorder the terms:
3(-5 + x) + x = 4(x + -4) + 1
(-5 * 3 + x * 3) + x = 4(x + -4) + 1
(-15 + 3x) + x = 4(x + -4) + 1

Combine like terms: 3x + x = 4x
-15 + 4x = 4(x + -4) + 1

Reorder the terms:
-15 + 4x = 4(-4 + x) + 1
-15 + 4x = (-4 * 4 + x * 4) + 1
-15 + 4x = (-16 + 4x) + 1

Reorder the terms:
-15 + 4x = -16 + 1 + 4x

Combine like terms: -16 + 1 = -15
-15 + 4x = -15 + 4x

Add '15' to each side of the equation.
-15 + 15 + 4x = -15 + 15 + 4x

Combine like terms: -15 + 15 = 0
0 + 4x = -15 + 15 + 4x
4x = -15 + 15 + 4x

Combine like terms: -15 + 15 = 0
4x = 0 + 4x
4x = 4x

Add '-4x' to each side of the equation.
4x + -4x = 4x + -4x

Combine like terms: 4x + -4x = 0
0 = 4x + -4x

Combine like terms: 4x + -4x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -10x-12=-2-4(3x+8) | | 1x+25=7x+15 | | -2(7-x)+4=-4 | | 5b+6=b+14 | | 5/5-(5-5)= | | 3(x+2)=2(4x-3) | | 2=10(x+9)+6x | | 5x-22/6+x/30=x/5-1 | | 62.9296(y-100)+64.9278=63.546 | | 3x+5-40=125 | | 9c^2-4c^2+2c^2= | | 1/3(-5) | | 46-x=27 | | 4/21+1/7= | | 2(7-x)+4=-4 | | -6(x-5)=50-2x | | 5/5+6-z/2= | | 9-3m+mn-3n= | | 62.9296(100-y)+64.9278=63.546 | | -8x-9=23 | | 8t=7t+2/3 | | -11-4t=6+3(11-3t) | | 2x^2-5+167=0 | | -(1+7v)-7b=111 | | 14x+22=7x-1 | | x(x-4)=x+5x+8 | | 10h-7=9h-26 | | X=96+7x | | 42=6-2/3x | | 7/10d-21/10 | | 4x-70=12y+2 | | 4p^2-2-p=2-p |

Equations solver categories